An exploration to preferred and non-preferred body parts in university students - Chacón Araya, Yamileth (2015)
The purpose of the study was to describe the anatomical preferences of students from an university located in Central America. Participants were university females (n = 259, mean age, height, weight and BMI = 18.8 ± 2.9 yr., 159.6 ± 5.9 cm, 57.6 ± 11.9 kg, and 22.6 ± 4.3 kg/m2 , respectively) and males (n = 263; mean age, height, weight and BMI = 18.9 ± 2.5 yr., 172.9 ± 6.3 cm, 69.0 ± 13.1 kg, and 23.0 ± 3.8 kg/m2 , respectively). Participants rated their preferred and non-preferred body parts with a questionnaire. For both genders, the head, neck and face zones were the preferred anatomical area and the non-preferred anatomical areas were the torso and abdomen. Body mass index (BMI) was positively correlated to non-preferred body parts in females (r = 0.164, p = 0.008). In males, BMI was positively correlated to their preferred body parts (r = 0.160, p = 0.009). In conclusion, students from a Central American university rated similarly their preferred but differently their nonpreferred anatomical parts.